The prevalence of sensory changes in post-COVID syndrome: A systematic review and meta-analysis - Trott, Mike; Driscoll, Robin; Pardhan, Shahina (Frontiers in Medicine, 2022)
Post-COVID syndrome can be defined as symptoms of COVID-19 that persist for longer than 12 weeks, with several studies reporting persistent symptoms relating to the sensory organs (eyes, ears, and nose). The aim of this systematic review was to examine the prevalence of persistent anosmia, hyposmia, ageusia, and hypogeusia, as well as eye/vision and ear/hearing related long-COVID symptoms. Authors searched the electronic databases from inception to November 2021. Search terms included words related to long-COVID, smell, taste, eyes/vision, and ears/hearing, with all observational study designs being included. A random effects meta-analysis was undertaken, calculating the prevalence proportions of anosmia, hyposmia, ageusia, and hypogeusia, respectively. From the initial pool, 21 studies met the inclusion criteria (total n 4,707; median n per study 125; median age = 49.8; median percentage female = 59.2%) and 14 were included in the meta-analysis The prevalence of anosmia was 12.2% (95% CI 7.7–16.6%), hyposmia 29.9% (95% CI 19.9–40%), ageusia 11.7% (95% CI 6.1–17.3%), and hypogeusia 31.2% (95% 16.4–46.1%). Several eye/vision and ear/hearing symptoms were also reported. Considering that changes in the sensory organs are associated with decreases in quality of life, future research should examine the etiology behind the persistent symptoms. Systematic review registration [www.crd.york.ac.uk/prospero], identifier [CRD42021292804].